ANALISIS MODEL ANTRIAN PADA STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) LILIBA - Febyana Wolla; Christien C Foenay; Tarsisius Timuneno (Universitas Nusa Cendana, 2019)
The purpose of this research is to know the performance of queue service and to find solutions to overcoming queues at Liliba gas station. This study using the observation method. Based on the observation data obtained and then set up a calculation of the observed system. The data analysis method uses multiple line queue models (Single Channel – Multi Phase). Data in the analysis is descriptively quantitative and qualitative. The results derived from such calculations are noticeable that there is a queue in the afternoon. So that the solution is given that in the period of busy time or at the time there is a long queue, companies should divert motorcycle customers to the car line if on the car line there is no queue, so it can improve efficiency of service at Liliba gas station. Keywords : Queueing Theory, Queueing Model